EXPLORING CHALLENGES AND OPPORTUNITIES IN INTERCULTURAL LEARNING MATERIALS FOR EFL IN HIGHER EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Eripuddin; Zeinab Abu Samak; Pipit Rahayu; Jufrizal Jufrizal (English Study Program University of Pasir Pengaraian, 2026)
This study explores the challenges and opportunities associated with intercultural learning materials in English as a Foreign Language (EFL) higher education through a systematic literature review. The study aims to provide a comprehensive understanding of how intercultural materials are developed, implemented, and evaluated in contemporary educational contexts. Using a systematic review approach, relevant studies published between 2020 and 2025 were identified, screened, and analyzed based on predefined inclusion criteria. The findings reveal that the implementation of intercultural learning materials is constrained by several interconnected challenges, including limited teacher competence, rigid institutional structures, and the lack of culturally diverse and contextually relevant materials. These challenges indicate that intercultural learning has not yet been fully integrated into mainstream EFL instruction. However, the study also identifies significant opportunities, particularly in the use of digital technologies, the integration of local and multicultural content, and the adoption of innovative pedagogical approaches such as experiential and drama-based learning. These opportunities provide pathways for enhancing students’ intercultural communicative competence and creating more meaningful learning experiences. The study highlights the importance of aligning global perspectives with local cultural contexts, especially in institutions such as Universitas Pasir Pengaraian (UPP). Overall, this study contributes to the literature by offering a systematic synthesis of recent research and providing practical implications for educators, curriculum developers, and policymakers . It also suggests directions for future research on the sustainability and scalability of intercultural learning materials in higher education.